Effectiveness of Zakat, Infaq and Sadaqah Distribution at BAZNAS North Lombok Regency - Azra', Kurniawan; Azizah, Lina; Nirwana, Baiq Elok (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2026)
This study aims to analyze in depth the effectiveness of zakat, infak, sadaqah (ZIS) funds distribution at the Zakat Management Agency in North Lombok Regency. The method used in this research is a quantitative method, with secondary data sources, where the data collection technique uses a time series of data a period of 2021-2025. The data for which was obtained from BAZNAS North Lombok Regency financial report. The population of this study consists of all financial reports of BAZNAS North Lombok Regency. Meanwhile, the sample used to measure effectiveness is based on specific criteria, namely financial reports that have been published on the official website and audited. In this study, the sample comprises the financial reports of BAZNAS North Lombok Regency from 2021 to 2025. The data collection technique employed is documentation. The data analysis technique utilizes effectiveness measurement through the Allocation to Collection Ratio (ACR). The results obtained from this study are the distribution of zakat funds in BAZNAS, North Lombok Regency, which is distributed to 8 ashnaf such as the indigent, the poor, amil zakat, converts, slaves, debtors, fisabilillah, and ibn sabil. Meanwhile, infaq and alms funds can be distributed to everyone outside the ashnaf of zakat funds. The effectiveness of the distribution of ZIS funds to BAZNAS in North Lombok Regency in 2021 was 104%, in 2022 it was 104%, in 2023 it was 100%, in 2024 it was 94%, and in 2025 it was 105%, so with the percentage above, the distribution of BAZNAS is included in the highly effective ACR category. This means that the distribution of ZIS funds at BAZNAS North Lombok Regency is very effective.